2020
DOI: 10.3389/fmicb.2020.00428
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Glutamine Synthetase-Coding Gene glnA Increases Susceptibility to Quinolones Through Increasing Outer Membrane Protein F in Salmonella enterica Serovar Typhi

Abstract: Ciprofloxacin is the choice treatment for infections caused by Salmonella Typhi, however, reduced susceptibility to ciprofloxacin has been reported for this pathogen. Considering the decreased approbation of new antimicrobials and the crisis of resistance, one strategy to combat this problem is to find new targets that enhances the antimicrobial activity for approved antimicrobials. In search of mutants with increased susceptibility to ciprofloxacin; 3,216 EZ-Tn5 transposon mutants of S. Typhi were screened. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Here we showed that the twitching and virulence phenotypes that were altered in the lip1 - mutant could be restored to wild-type levels by in trans expression of lip1 , but not of ompW . These results demonstrate that the observed phenotypes were a direct consequence of lip1 disruption and not due to a polar effect on ompW expression, as sometimes observed in transposon-mediated mutagenesis, including with EZ-Tn5 [ 66 ]. With that said, it is yet to be elucidated whether there is a functional relationship between Lip1 and OmpW.…”
Section: Discussionsupporting
confidence: 68%
“…Here we showed that the twitching and virulence phenotypes that were altered in the lip1 - mutant could be restored to wild-type levels by in trans expression of lip1 , but not of ompW . These results demonstrate that the observed phenotypes were a direct consequence of lip1 disruption and not due to a polar effect on ompW expression, as sometimes observed in transposon-mediated mutagenesis, including with EZ-Tn5 [ 66 ]. With that said, it is yet to be elucidated whether there is a functional relationship between Lip1 and OmpW.…”
Section: Discussionsupporting
confidence: 68%
“…One mutant had a stop codon following the second residue (glnA 2 Ser->STOP , C5A), strongly suggesting the protein is non-functional as it is so severely truncated. In a recent study in Salmonella enterica serovar Typhi, it was shown that deletion of glnA greatly increased expression of the NtrBC two-component system [53]. Taylor et al [25] showed in their expression analyses of the model system used in this study that the means through which motility was initially restored was via hyper-activation of NtrC.…”
Section: Discussionmentioning
confidence: 69%
“…One mutant had a stop codon following the second residue (glnA 2 Ser->STOP , C5A), heavily suggesting the protein is non-functional as it is so severely truncated. In a recent study in Salmonella enterica Serovar Typhi, it was shown that deletion of glnA greatly increased expression of the NtrBC two component system (46). Taylor et al (25) showed in their expression analyses of the model system used in this study that the means through which motility was initially restored was via hyper activation of NtrC.…”
Section: Discussionmentioning
confidence: 70%